Hubungan antara Kecerdasan Spiritual dengan Regulasi Emosi pada Mahasiswa Fakultas Sains, Teknologi, dan Kesehatan Universitas Sahid Surakarta - Bilqiis Al-Ghaadah Santifa; Sri Ernawati; Dhian Riskiana Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study is motivated by the importance of emotion regulation skills among university students who are in the transitional phase toward early adulthood, where academic, social, and personal pressures can affect psychological well-being. Spiritual intelligence is considered one of the factors that can support this ability. The purpose of this study is to determine the relationship between spiritual intelligence and emotion regulation among students of the Faculty of Science, Technology, and Health, Universitas Sahid Surakarta. This research employed a quantitative method with a correlational design. The sample consisted of 196 students selected through purposive sampling. The research instruments were a spiritual intelligence scale and an emotion regulation scale, both of which had been tested for validity and reliability. Data were analyzed using Pearson Product Moment correlation. The results showed a very strong and significant positive relationship between spiritual intelligence and emotion regulation (r = 0.883; p < 0.05). These findings indicate that the higher the students’ spiritual intelligence, the better their ability to recognize, evaluate, and manage emotions. The implications of this study emphasize the importance of developing spiritual intelligence in higher education settings as an effort to enhance students’ emotion regulation abilities.